Effect of Malva Nut Gel as Fat Replacer on Sponge Cake - Chysirichote, Teeranuch; Suanpang, Pannee; Buntham, Piramal (Journal of Food Health and Bioenvironmental Science, 2023)
Malva nut originated in Southeast Asia and is cultivated in the Eastern part of Thailand. Gel prepared from its mature seed coat containing high water-soluble dietary fiber was used as a fat replacer in this research. Part of the butter (25-50%) and milk (10-20%) for the sponge cake were replaced with malva nut gel. Physical, chemical and organoleptic analyses were conducted to evaluate the effects of malva nut gel on the properties of the sponge cake. For specific volume, all samples were not significantly different (p>0.05); moreover, the roughness, lightness (L*) and yellowness (b*) of the crust increased while the values of the crumb decreased. In the final product obtained from this research 10% of the milk and 25% of the butter were replaced with malva nut gel, which was the highest replacement content of butter and milk with a high customer acceptance. Its chemical composition consisted of 22.72% moisture, 6.28% protein, 16.20% fat, 0.90% ash, 53.90% carbohydrate and 3.76% dietary fiber. Cholesterol and total calories were 114.22 mg and 386.52 Kcal, respectively. The content of fat, carbohydrate, cholesterol, and total calories of this product were lower than the basic formula (p ≤ 0.05). In addition, 120 consumers accepted this cake in terms of appearance, color, aroma, taste, softness and rated it overall, as ‘very much liking’ and the aftertaste as ‘moderate liking’.